Association Between Hepatitis C Virus and Head and Neck Cancers - Mahale, Parag; Sturgis, Erich M.; Tweardy, David J.; Ariza-Heredia, Ella J.; Torres, Harrys A. (JNCI : Journal of the National Cancer Institute, 2016)
Hepatitis C virus (HCV) infection is associated with hepatocellular carcinoma and non-Hodgkin's lymphoma. In 2009, MD Anderson established the first US clinic for treating HCV-infected cancer patients, where we observed an unexpectedly large number of patients with head and neck cancers (HNCs). We sought to determine whether HCV is associated with HNCs. In this case-control study, medical records of cancer patients tested for HCV antibodies at our center from 2004 through 2014 were identified. Case subjects had new-onset primary oropharyngeal or nonoropharyngeal (oral cavity, nasopharynx, hypopharynx, or larynx) HNCs. Control subjects had smoking-associated (lung, esophagus, or urinary bladder) cancers. Biopsy reports of oropharyngeal cancers tested for human papillomavirus (HPV) were reviewed. Patients with lymphoma were excluded. Multivariable logistic regression models were constructed. All statistical tests were two-sided. Of 34 545 cancer patients tested for HCV antibodies, 409 case subjects (164 oropharyngeal and 245 nonoropharyngeal) and 694 control subjects (378 lung, 168 esophagus, and 148 urinary bladder) were studied. The prevalence of HCV seropositivity was higher in oropharyngeal cancer patients (14.0%, 95% confidence interval [CI] = 8.7% to 19.4%, vs 6.5%, 95% CI = 4.6% to 8.3%), particularly HPV-positive oropharyngeal cancer patients (16.9%, 95% CI = 8.7% to 24.9%, vs 6.5%, 95% CI = 4.6% to 8.3%), and nonoropharyngeal HNC patients (20.0%, 95% CI = 14.9% to 25.0%, vs 6.5%, 95% CI = 4.6% to 8.3%) than in control subjects. Adjusted models showed a statistically significant association of HCV seropositivity with nonoropharyngeal (except nasopharyngeal) HNCs (odds ratio [OR] = 2.85, 95% CI = 1.38 to 5.88) and HPV-positive oropharyngeal cancers (OR = 2.97, 95% CI = 1.31 to 6.76). HCV is associated with nonoropharyngeal (except nasopharyngeal) and HPV-positive oropharyngeal HNCs. Further studies are required to explore the possible interaction between HCV and HPV, and the association between HCV and other HPV-related malignancies.